Fixed-dose combination for adults accessing antiretroviral therapy - SA HIV Clinicians Society (AOSIS, 2013)
This document serves to guide clinicians and programme managers on how to switch from 3 separate antiretroviral (ARV) drugs to the new, single, fixed-dose combination (FDC) tablet containing tenofovir (TDF), emtricitabine (FTC) and efavirenz (EFV). Summary Transitioning from individual drugs to an FDC tablet needs to be managed carefully, particularly regarding stock management, ordering processes, supply-chain integrity and comprehensive patient counselling. Priority groups • Initially, FDC supply will be insufficient to provide for all FDC-suitable patients • Therefore, the National Department of Health (NDoH) has recommended that the following patient groups be prioritized for FDC initiation/switch: • Priority group 1: All HIV-positive patients newly initiating ART - adults, adolescents and pregnant women (regardless of CD4 count (amendment to the guidelines for the prevention of mother-to-child transmission of HIV (PMTCT) anticipated in April 2013) - and who do not have contra-indications to the FDC component drugs • Priority group 2: HIV-positive pregnant women and breastfeeding mothers currently stable on lamivudine (3TC), TDF and EFV • Priority group 3: Virologically suppressed patients on a stavudine (d4T)-based regimen and who have normal renal function • Priority group 4: Stable patients receiving individual TDF, 3TC and EFV and who have tuberculosis (TB) co-infection • Priority group 5: Stable patients receiving individual TDF, 3TC and EFV and who have other co-morbidites (e.g. hypertension, diabetes) • Priority group 6: Patients receiving individual TDF, 3TC and EFV and who request to switch to the FDC treatment • Priority group 7: Patients receiving individual TDF, 3TC and EFV and who, after counselling, agree to switch to the FDC treatment. Important: Clinic staff must co-ordinate this process and only switch as many patients to the FDC tablet as stock allows. This should avoid patients being switched back and forth between FDC and individual drugs due to insufficient stock. Note: The FDC tablet is not significantly larger than EFV or lopinavir/ritonavir (LOP/r) (Aluvia); therefore, swallowing should not be problematic. S Afr J HIV Med 2013;14(1 Suppl):41-43. DOI:10.7196/SAJHIVMED.913